MOF-derived high-entropy alloy electrocatalyst for nitrate reduction to ammonia and preparation method thereof

CN122707171APending Publication Date: 2026-09-08SHANDONG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611157548.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-09-08

AI Technical Summary

Technical Problem

[0003]具体而言,现有技术公开的高熵合金体系在元素组成选择上缺乏针对硝酸根还原反应路径的特异性适配,未能精准匹配*NO3吸附活化及后续加氢脱氧过程对活性位点电子结构的特殊要求;同时,载体材料通常仅作为惰性导电支撑,缺乏与活性组分协同优化界面微环境的功能性设计,难以在提升结构稳定性的同时促进水解离以提供活性氢物种

Benefits of technology

本发明提供了一种MOF衍生的高熵合金电催化硝酸根还原制氨催化剂,通过精准设计FeCoNiCuMo五元高熵合金活性中心与ZnO氮掺杂多孔六方碳(ZnO-NHC)多功能载体的协同结构,实现了性能的突破性提升。在活性组分设计上,Fe、Co、Ni、Cu、Mo五元等摩尔组分的鸡尾酒效应精准优化了d带中心:其中Mo位点凭借对氧中间体的强亲和力显著降低了NO3-吸附与活化能垒,Cu位点有效阻断了N-N偶联路径以抑制N2生成,而Fe/Co/Ni则协同促进NHx中间体的加氢脱氧过程,这种电子结构匹配大幅提升了反应动力学并抑制了析氢副反应;在载体功能上,ZnO-NHC不仅完整保留了MOF前驱体的六方空心框架以提供高比表面积与优异导电网络,其表面分散的ZnO纳米颗粒更能作为助催化剂促进界面水解离提供活性氢物种,进一步加速加氢步骤。得益于此,该催化剂在0.1 mol/L KNO3和0.1 mol/L Na2SO4的中性混合电解液中,-0.8 V vs. RHE电位下实现了92.6%的法拉第效率与3469.12 µg·h-1·mg-1cat.的氨产率;同时,ZnO-NHC载体的限域作用与焦耳热制备的高分散合金颗粒赋予了催化剂卓越的结构稳定性,在30小时连续电解及15次循环测试中性能几无衰减,为电催化硝酸根还原制氨的工业化应用奠定了基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122707171A_ABST
    Figure CN122707171A_ABST
Patent Text Reader

Abstract

The application discloses a MOF-derived high-entropy alloy electrocatalytic nitrate reduction ammonia catalyst and a preparation method, and belongs to the technical field of electrocatalytic materials and environmental energy catalysis. The catalyst comprises a carrier and high-entropy alloy nanoparticles loaded on the surface of the carrier; the carrier is ZnO nitrogen-doped porous hexagonal carbon, and the high-entropy alloy is composed of five elements of Fe, Co, Ni, Cu and Mo in equal molar ratio. The high porosity, good conductivity and excellent electrochemical electrolysis stability of the carrier provide basic performance guarantee and a large number of attachment positions for the high-entropy alloy nanoparticles loaded on the surface, and increase the electrochemical active surface area. In the process of electrocatalytic nitrate reduction ammonia, the electrocatalyst effectively improves the reaction efficiency, and the application focuses on a non-noble metal catalyst which is low in production cost, environmentally friendly and easy to popularize, thereby greatly promoting the application of the catalyst in the actual electrocatalytic field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrocatalytic materials and environmental energy catalysis technology, specifically relating to a MOF-derived high-entropy alloy electrocatalytic catalyst for the reduction of nitrate to ammonia and its preparation method. Background Technology

[0002] Electrocatalytic nitrate reduction (NO3RR) is a crucial technological pathway for the treatment of nitrate pollution in water bodies and the green synthesis of ammonia. The core challenge lies in overcoming the slow reaction kinetics in an aqueous environment and effectively suppressing hydrogen evolution side reactions to obtain high-value-added ammonia products. Although high-entropy alloys have shown application potential in this field due to their multi-principal-component synergistic effects, and various high-entropy alloy catalysts have been disclosed in existing technologies, current solutions still face a fundamental technical bottleneck.

[0003] Specifically, existing high-entropy alloy systems lack specific adaptations to the nitrate reduction reaction pathway in their elemental composition selection, failing to precisely match the specific requirements of *NO3 adsorption activation and subsequent hydrodeoxygenation processes for the electronic structure of active sites. Simultaneously, the support materials typically serve only as inert conductive supports, lacking functional designs that synergistically optimize the interfacial microenvironment with the active components, making it difficult to simultaneously improve structural stability and promote water dissociation to provide active hydrogen species. This dual deficiency in both the chemical composition of the active components and the functional design of the support prevents existing catalysts from simultaneously achieving high catalytic activity, excellent ammonia selectivity, and long-term operational stability, severely restricting the practical application of this technology. Summary of the Invention

[0004] To address the shortcomings of existing technologies, the present invention aims to provide a MOF-derived high-entropy alloy electrocatalytic catalyst for the reduction of nitrate to ammonia and its preparation method.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows: In a first aspect, the present invention provides a MOF-derived high-entropy alloy electrocatalytic catalyst for the reduction of nitrate to ammonia, comprising a support and high-entropy alloy nanoparticles supported on the surface of the support. The carrier is nitrogen-doped porous hexagonal carbon ZnO, and the high-entropy alloy is composed of five elements, Fe, Co, Ni, Cu and Mo, in equimolar ratios.

[0006] A second aspect of the present invention provides a method for preparing the MOF-derived high-entropy alloy electrocatalytic nitrate reduction to ammonia catalyst described in the first aspect, comprising: A precursor was obtained by mixing a 2,5-dihydroxyterephthalic acid solution and a zinc source solution and then carrying out a hydrothermal reaction. The precursor was pyrolyzed under a nitrogen atmosphere to obtain nitrogen-doped porous hexagonal carbon ZnO. Nitrogen-doped porous hexagonal carbon ZnO was mixed with Fe, Co, Ni, Cu and Mo salts in an equimolar ratio to obtain a mixed powder. The mixed powder was heat-treated using a Joule heating device under a protective atmosphere at a heating rate of 10°C. 3 -10 4 A high-entropy alloy electrocatalyst for the reduction of nitrate to ammonia was obtained by heating at ℃ / s, with a heating temperature of 1100-1300℃ and a heating time of 0.1-1 s.

[0007] A third aspect of the present invention provides the application of the MOF-derived high-entropy alloy electrocatalytic nitrate reduction ammonia production catalyst described in the first aspect in the electrocatalytic nitrate reduction ammonia production process.

[0008] A fourth aspect of the present invention provides a method for electrocatalytic reduction of nitrate to produce ammonia, comprising: The MOF-derived high-entropy alloy electrocatalyst for the reduction of nitrate to ammonia described in the first aspect is used as the catalytically active component for the reduction of nitrate to ammonia in a neutral electrolyte system, thereby reducing nitrate ions in nitrate solution to ammonia.

[0009] The beneficial effects of this invention are as follows: This invention provides a MOF-derived high-entropy alloy electrocatalyst for the reduction of nitrate to ammonia. A breakthrough performance improvement is achieved through the precise design of a synergistic structure between the FeCoNiCuMo quinary high-entropy alloy active center and the ZnO nitrogen-doped porous hexagonal carbon (ZnO-NHC) multifunctional support. In terms of active component design, the cocktail effect of equimolar quinary components (Fe, Co, Ni, Cu, Mo) precisely optimizes the d-band center: the Mo sites significantly reduce NO3- concentration due to their strong affinity for oxygen intermediates. - The adsorption and activation barriers effectively block the N-N coupling pathway at Cu sites to inhibit N2 generation, while Fe / Co / Ni synergistically promote NH4+ generation. x In the hydrogenation and deoxygenation process of the intermediate, this electronic structure matching significantly improved the reaction kinetics and suppressed the hydrogen evolution side reaction. In terms of support function, ZnO-NHC ​​not only fully retains the hexagonal hollow framework of the MOF precursor to provide a high specific surface area and excellent conductive network, but its surface-dispersed ZnO nanoparticles also act as a co-catalyst to promote interfacial water dissociation and provide active hydrogen species, further accelerating the hydrogenation step. Thanks to this, the catalyst achieved a Faraday efficiency of 92.6% and a hydrogen peroxide concentration of 3469.12 µg·h⁻¹ in a neutral mixed electrolyte of 0.1 mol / L KNO₃ and 0.1 mol / L Na₂SO₄ at -0.8 V vs. RHE potential. -1 ·mg -1 cat.The catalyst exhibits excellent structural stability due to the confinement effect of the ZnO-NHC ​​support and the highly dispersed alloy particles prepared by Joule heating. Its performance showed almost no degradation during 30 hours of continuous electrolysis and 15 cycles, laying the foundation for the industrial application of electrocatalytic nitrate reduction to ammonia. Attached Figure Description

[0010] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0011] Figure 1 The images show the XRD patterns of the electrocatalysts prepared in Example 1 and Comparative Examples 1-4.

[0012] Figure 2 This is a scanning electron microscope image of the ZnO nitrogen-doped porous hexagonal carbon support prepared in Example 1.

[0013] Figure 3 This is a scanning electron microscope (SEM) image of the MOF-derived ZnO nitrogen-doped porous hexagonal carbon-supported FeCoNiCuMo pentagonal high-entropy alloy electrocatalyst prepared in Example 1.

[0014] Figure 4 This is a transmission electron microscope (TEM) image of the MOF-derived ZnO nitrogen-doped porous hexagonal carbon-supported FeCoNiCuMo pentagonal high-entropy alloy electrocatalyst prepared in Example 1.

[0015] Figure 5 The graph shows a comparison of the Faraday efficiency of the MOF-derived ZnO nitrogen-doped porous hexagonal carbon-supported FeCoNiCuMo pentagonal high-entropy alloy electrocatalysts prepared in Examples 1 and 1-4 at -0.8 V vs. RHE potential.

[0016] Figure 6 The graph shows a comparison of ammonia production rates of the MOF-derived catalysts prepared in Example 1 and Comparative Examples 1-4 at -0.8 V vs. RHE potential.

[0017] Figure 7 The long-term stability of the MOF-derived ZnO nitrogen-doped porous hexagonal carbon-supported FeCoNiCuMo pentagonal high-entropy alloy electrocatalyst prepared in Example 1 at -0.8 V vs. RHE potential.

[0018] Figure 8 The cycling stability of the MOF-derived ZnO nitrogen-doped porous hexagonal carbon-supported FeCoNiCuMo pentagonal high-entropy alloy electrocatalyst prepared in Example 1 at -0.8 V vs. RHE potential.

[0019] Figure 9The process flow diagram for preparing the MOF-derived high-entropy alloy electrocatalytic nitrate reduction to ammonia catalyst provided by the present invention is shown. Detailed Implementation

[0020] In existing electrocatalytic nitrate reduction technologies, high-entropy alloy catalysts cannot simultaneously achieve high activity, high ammonia selectivity, and long-term stable operation due to the lack of specific elemental composition tailored to the reaction pathway and the limited functionality of the support. While existing technologies have attempted to combine high-entropy alloys with MOF-derived carbon materials, the active components typically lack precise electronic structure modulation for NO3 adsorption activation and hydrodeoxygenation processes, and the supports often function as inert conductive frameworks, making it difficult to effectively suppress hydrogen evolution side reactions and improve interfacial reaction kinetics. Therefore, this invention proposes a MOF-derived high-entropy alloy electrocatalytic nitrate reduction catalyst for ammonia production and its preparation method.

[0021] A first typical embodiment of the present invention provides a MOF-derived high-entropy alloy electrocatalytic nitrate reduction to ammonia catalyst (FeCoNiCuMo@ZnO-NHC), comprising a support and high-entropy alloy nanoparticles supported on the surface of the support; The carrier is nitrogen-doped porous hexagonal carbon ZnO, and the high-entropy alloy is composed of five elements, Fe, Co, Ni, Cu and Mo, in equimolar ratios.

[0022] The FeCoNiCuMo@ZnO-NHC ​​high-entropy alloy electrocatalyst provided by this invention combines the advantages of the three-dimensional porous conductive network of the ZnO-NHC ​​support with the multi-element synergistic effect of the high-entropy alloy, exhibiting excellent electrocatalytic activity, selectivity, and long-term stability in the reduction of nitrate to ammonia.

[0023] This electrocatalyst is a catalyst system composed of a quinary equimolar high-entropy alloy of Fe, Co, Ni, Cu, and Mo, and nitrogen-doped porous hexagonal carbon ZnO (ZnO-NHC). Through careful selection of specific element combinations, the active sites are precisely regulated using a multi-principal cocktail effect: the cocktail effect of the quinary equimolar composition of Fe, Co, Ni, Cu, and Mo precisely optimizes the d-band center. Specifically, the Mo site significantly reduces the NO3- adsorption and activation energy barrier due to its strong affinity for oxygen intermediates; the Cu site effectively blocks the N-N coupling pathway to inhibit N2 formation; and Fe / Co / Ni synergistically promote NH4+. xIn the hydrogenation and deoxygenation process of the intermediate, this electronic structure matching significantly improved the reaction kinetics and suppressed the hydrogen evolution side reaction. Functionally, ZnO-NHC ​​not only fully retains the hexagonal hollow framework of the MOF precursor to provide a high specific surface area and excellent conductive network, but its surface-dispersed ZnO nanoparticles also act as a co-catalyst to promote interfacial water dissociation and provide active hydrogen species, further accelerating the hydrogenation step. Simultaneously, the ZnO-NHC ​​support not only retains the porous confined structure of the MOF precursor to improve conductivity and dispersibility, but its surface ZnO component also acts as a co-catalyst to promote water dissociation and provide active hydrogen, significantly accelerating the reaction process. Combined with the highly uniform dispersion of alloy nanoparticles achieved by the rapid Joule heating method, this catalyst achieved a Faraday efficiency of 92.6% and a hydrogen emission rate of 3469.12 µg·h⁻¹ in a neutral electrolyte. -1 ·mg -1 cat. The ammonia yield was improved and excellent stability was maintained during the 30-hour test, providing a practical technical solution for the industrial application of electrocatalytic nitrate reduction to produce ammonia.

[0024] In this invention, the diameter of the high-entropy alloy nanoparticles is 30-40 nm.

[0025] The diameter of 30-40 nm is small enough to ensure that the high-entropy alloy nanoparticles are highly dispersed within the confined channels of the ZnO-NHC ​​porous carbon support, maximizing the exposure of the five-membered active sites of FeCoNiCuMo and increasing the electrochemical active surface area, thereby accelerating the NO3-reactive gas exchange process. - Adsorption with NH x Hydrogenation kinetics. Furthermore, the particle size should not be too small (e.g., <10 nm, which easily leads to Ostwald ripening or agglomeration through carbon layer migration during long-term liquid-phase operation). Particles of 30-40 nm can maintain structural anchoring within the hexagonal hollow framework of ZnO-NHC. Combined with the strong interfacial interaction between ZnO and nitrogen-doped carbon, this prevents particle shedding or agglomeration during long-term electrolysis, thus improving catalyst stability.

[0026] In this invention, the loading of the high-entropy alloy nanoparticles is determined by the feed ratio of nitrogen-doped porous hexagonal carbon ZnO to the metal salt precursor. The mass ratio of the nitrogen-doped porous hexagonal carbon ZnO to the total mass of the metal salt precursor is (0.8-1.2):1.2. Preferably, the mass ratio of the nitrogen-doped porous hexagonal carbon ZnO to the metal salt precursor is 1.0:1.2.

[0027] In this invention, the high-entropy alloy nanoparticles have a face-centered cubic (fcc) crystal structure, and the elements are highly uniformly distributed on the surface of the carrier without obvious elemental segregation.

[0028] Understandably, the face-centered cubic (fcc) crystal structure is direct evidence of the stable existence of multi-principal solid solutions in high-entropy alloys, indicating that the five elements Fe, Co, Ni, Cu, and Mo have truly achieved atomic-level homogeneous alloying under Joule heating instantaneous high temperatures rather than simple physical mixing or phase separation; the close-packed planes of the fcc structure (such as the (111) plane) have abundant low-coordination active sites, and its d-band center can be continuously adjusted through the cocktail effect of the five-element components, which perfectly matches NO3. - The multi-step reaction pathway of adsorption activation (Mo contribution) - NO2 / NO hydrogenation (Fe / Co / Ni contribution) - inhibition of NN coupling (Cu contribution) imposes different requirements on the adsorption and desorption energies of each intermediate, thereby suppressing the NO3RR overpotential and raising the HER competition threshold from the perspective of intrinsic electronic structure.

[0029] In this invention, the nitrogen-doped porous hexagonal carbon ZnO retains the hexagonal rod-like morphology of Zn-MOF-74.

[0030] The preservation of the hexagonal rod-like morphology of Zn-MOF-74 ensures that the ZnO-NHC ​​support is not ordinary nitrogen-doped carbon, but rather fully inherits the one-dimensional hexagonal hollow rod framework and hierarchical porous network of the precursor. The high specific surface area and open channels provided by the hollow rod structure are beneficial for electrolyte mass transfer and bubble desorption, and can also form a geometric confinement for 30-40 nm high-entropy alloy particles, preventing particle migration and agglomeration during long-term electrolysis. More importantly, the morphology preservation means that Zn species have not been completely reduced and removed, but are dispersed in situ in the nitrogen-doped carbon framework in the form of ZnO nanoclusters. This maintains the conductivity and mechanical stability of the support, and promotes water dissociation and H-donation through the three-phase interface of ZnO-carbon-high-entropy alloy, forming a spatial coupling of adsorption activation-hydrogen supply with the active sites of fcc high-entropy alloy.

[0031] A second typical embodiment of the present invention provides a method for preparing the MOF-derived high-entropy alloy electrocatalytic nitrate reduction to ammonia catalyst, comprising: A precursor was obtained by mixing a 2,5-dihydroxyterephthalic acid solution and a zinc source solution and then carrying out a hydrothermal reaction. The precursor was pyrolyzed under a nitrogen atmosphere to obtain nitrogen-doped porous hexagonal carbon ZnO. Nitrogen-doped porous hexagonal carbon ZnO was mixed with Fe, Co, Ni, Cu and Mo salts in an equimolar ratio to obtain a mixed powder. Under a protective atmosphere, the mixed powder is rapidly heat-treated using a Joule heating device, taking advantage of the device's ultra-fast heating capacity (heating rate of 10). 3 -10 4 (℃ / s), heating temperature 1100-1300℃, heating time 0.1-1 s, to obtain MOF-derived high-entropy alloy electrocatalytic nitrate reduction to ammonia catalyst.

[0032] Understandably, the term heating time refers to the holding time after reaching the target temperature, that is, holding the temperature for 0.1-1 seconds after heating to 1100-1300℃.

[0033] The FeCoNiCuMo@ZnO-NHC ​​high-entropy alloy electrocatalyst prepared by this invention can efficiently electrocatalyze the reduction of nitrate to ammonia in a neutral electrolyte system, effectively suppressing the hydrogen evolution side reaction and exhibiting excellent electrochemical durability.

[0034] In this invention, the hydrothermal reaction following mixing the 2,5-dihydroxyterephthalic acid solution and the zinc source solution includes: Dissolve 2,5-dihydroxyterephthalic acid in a mixed solution of water and N,N-dimethylformamide (DMF), and stir until completely dissolved to form solution A; Dissolve zinc acetate dihydrate in a mixed solution of water and N,N-dimethylformamide, and stir until completely dissolved to form solution B; While stirring, pour solution A into solution B, continue stirring, and a mixed solution is obtained; The mixed solution was subjected to a hydrothermal reaction, and after the reaction was completed, it was naturally cooled to room temperature to obtain the precursor.

[0035] The crystallinity and morphology of the precursor determine the integrity of the support structure, the dispersion of the active component, and the interfacial synergistic efficiency, ultimately affecting the activity, selectivity, and stability of the electrocatalyst. To obtain a Zn-MOF-74 precursor with high crystallinity and uniform morphology, this invention uses a Zn-MOF-74-specific ligand-zinc source system of 2,5-dihydroxyterephthalic acid and zinc acetate dihydrate. By controlling the water / DMF mixed solvent and using a specific feeding sequence of the ligand solution into the zinc source solution, a hexagonal rod-shaped hollow precursor with high crystallinity and uniform morphology can be grown under hydrothermal high temperature and high pressure conditions. This precursor not only provides the structural basis for subsequent nitrogen atmosphere pyrolysis, ensuring that the hexagonal porous framework is fully preserved during carbonization to achieve geometric confinement of high-entropy alloy particles, but also promotes the in-situ transformation of remaining Zn species into uniformly dispersed ZnO nanoclusters and achieves in-situ nitrogen doping with the help of nitrogen to build a conductive network. This fundamentally avoids problems such as pore blockage of the support, Zn agglomeration, or nitrogen doping failure caused by poor crystallinity and uneven morphology of the precursor. It provides indispensable structural and functional support for the uniform loading and interfacial synergistic catalysis of subsequent FeCoNiCuMo high-entropy alloys.

[0036] If the obtained precursor has poor crystallinity and uneven morphology, its morphology will collapse after pyrolysis, losing its ability to confine high-entropy alloy particles. Zn will agglomerate into large particles, losing its co-catalytic effect of promoting water dissociation. Or, uneven nitrogen doping will lead to poor conductivity. These problems will directly prevent the support from forming a synergistic relationship with the FeCoNiCuMo pentagonal high-entropy alloy.

[0037] The mass ratio of the 2,5-dihydroxyterephthalic acid solution to zinc acetate dihydrate is 0.6:0.9-1.1, preferably 0.6:1.008. A slight excess of zinc prevents excessive ligand release, ensuring the crystallinity and purity of the MOF. Poor crystallinity leads to pore structure collapse after pyrolysis, reducing specific surface area and the loading of active sites.

[0038] The hydrothermal reaction is carried out at a temperature of 95-105℃ for a time of 20-30 hours.

[0039] This parameter window yields highly crystalline, uniformly morphologically uniform hexagonal rod-shaped Zn-MOF-74 precursors. A temperature of 95-105℃ ensures a matching coordination rate between 2,5-dihydroxyterephthalic acid and zinc acetate dihydrate, promoting the regular extension of the phenoxy-zinc coordination network to form hexagonal rod-shaped crystals. It also avoids insufficient crystal growth and residual free ligands leading to insufficient crystallinity due to excessively low temperatures, or excessive decomposition of DMF and Zn due to excessively high temperatures. 2+ Disordered coordination environment leads to impurities, bifurcated and agglomerated rod-shaped morphology, and other distortions. A duration of 20-30 hours can match the sufficient growth rhythm of hexagonal rod-shaped crystals, ensuring that the crystallinity of the precursor meets the standard and forms a uniform hollow rod-shaped structure. It can also avoid the problem of rod diameter being too thin due to too short a time, which makes it easy to collapse during pyrolysis, or rods becoming too coarse or even solid due to too long a time, which makes it difficult for subsequent high-entropy salts to penetrate into the interior and hinders the volatilization of internal Zn during pyrolysis, thus blocking the pores.

[0040] After the hydrothermal reaction is completed, the precipitate is separated, collected, and then washed and dried in sequence.

[0041] In this invention, the pyrolysis is carried out at a heating rate of 3-7℃ / min, a pyrolysis temperature of 750-850℃, and a pyrolysis time of 2-4 h. After the pyrolysis is completed, the product is naturally cooled to room temperature in the furnace, and then the product is taken out and ground to obtain ZnO nitrogen-doped porous hexagonal carbon.

[0042] Preferably, the pyrolysis is performed at a heating rate of 5°C / min, a pyrolysis temperature of 800°C, and a pyrolysis time of 3 h. After the pyrolysis is completed, the product is naturally cooled to room temperature in the furnace, and then the product is taken out and ground to obtain nitrogen-doped porous hexagonal carbon ZnO.

[0043] Within this parameter range, the heating rate can match the gradient decomposition rhythm of the precursor framework, avoiding excessively rapid heating that could lead to drastic ligand decomposition causing framework collapse and pore blockage, or excessively slow heating that could result in energy waste and excessive volatilization of Zn nodes. The pyrolysis temperature balances the degree of carbonization and the retention of Zn species. If the temperature is too low, the organic ligands cannot be fully carbonized to form a nitrogen-doped carbon framework with good conductivity; if the temperature is too high, Zn will be excessively reduced to elemental zinc and volatilized, preventing the in-situ formation of dispersed ZnO nanoclusters. The holding time ensures complete carbonization of the ligands and uniform incorporation of nitrogen atoms into the carbon lattice, while simultaneously enabling ZnO nanoclusters to nucleate and anchor stably in situ within the carbon framework. Combined with furnace cooling, this preserves the complete hexagonal rod-shaped hollow morphology and hierarchical pore structure. By controlling these parameters, a ZnO-NHC ​​support was obtained. This support not only constructed a highly conductive network through nitrogen doping, but also achieved geometric confinement of high-entropy alloy particles through a hexagonal hollow structure. Furthermore, the in-situ dispersed ZnO provided interfacial water dissociation active sites. This approach addresses the shortcomings of traditional carbon materials, such as poor conductivity and lack of co-catalytic function, at the support level, and provides necessary support for the uniform loading and synergistic electronic structure of subsequent FeCoNiCuMo high-entropy alloys.

[0044] In this invention, the salt is acetylacetone salt.

[0045] In this invention, the mixing of nitrogen-doped porous hexagonal carbon ZnO with equimolar amounts of Fe, Co, Ni, Cu, and Mo salts comprises: Weigh out nitrogen-doped porous hexagonal carbon ZnO and Fe, Co, Ni, Cu, and Mo acetylacetone salts in an equimolar ratio. The mass ratio of ZnO nitrogen-doped porous hexagonal carbon to the total mass of the target metal salts is (0.8-1.2):1.2. After weighing, add the mixture to an organic solvent, stir at 50-70℃, and dry to obtain a mixed powder.

[0046] The acetylacetone salts of Fe, Co, Ni, Cu, and Mo exhibit extremely high solubility in organic solvents, enabling homogeneous mixing at the molecular level. This ensures the simultaneous reduction and alloying of the five elements under subsequent Joule heating at high temperatures, avoiding elemental segregation or amorphous phase formation caused by uneven precursor distribution. This allows for the precise construction of pentagonal high-entropy alloy active centers with a face-centered cubic structure. By controlling the total mass ratio of ZnO-NHC ​​support to metal salt within the range of (0.8-1.2):1.2, coupled with stirring and drying at 50-70℃, capillary forces can be used to fully draw the metal precursor into the hexagonal hollow channels of the support, preventing metal salt agglomeration on the support surface. Simultaneously, a moderate loading level is maintained to avoid channel blockage and impeded mass transfer. The synergistic effect of this molecular-level premixing and pore-confined loading allows the 30-40 nm high-entropy alloy particles to be firmly anchored on the ZnO-NHC ​​support during the subsequent Joule heating process. This maximizes the exposure of the five synergistic active sites of FeCoNiCuMo and inhibits particle sintering through the strong interaction between the support and the metal.

[0047] The organic solvent is a C1-C3 alcohol, preferably anhydrous ethanol. This organic solvent can dissolve five acetylacetonate salts of Fe / Co / Ni / Cu / Mo, does not damage the hexagonal porous structure of ZnO-NHC, and leaves no difficult-to-remove residues in the pores after drying.

[0048] The third typical embodiment of the present invention provides the application of the MOF-derived high-entropy alloy electrocatalytic nitrate reduction to ammonia catalyst in the electrocatalytic nitrate reduction to ammonia process.

[0049] A fourth typical embodiment of the present invention provides a method for electrocatalytic reduction of nitrate to produce ammonia, comprising: The MOF-derived high-entropy alloy electrocatalytic nitrate reduction to ammonia catalyst is used as the catalytically active component for electrocatalytic nitrate reduction to ammonia, reducing nitrate ions in nitrate solution to ammonia in a neutral electrolyte system.

[0050] Electrocatalytic nitrate reduction is performed in a neutral electrolyte system, rather than the traditional strongly alkaline or acidic system. This significantly reduces pretreatment costs and equipment corrosion risks in industrial wastewater treatment, making it more suitable for practical applications. This neutral environment places more stringent requirements on the catalyst, as it lacks a high concentration of OH-. -With the aid of [unclear], the competition between the hydrogen evolution reaction (HER) and nitrate reduction becomes more intense, and nitrate concentrations are typically low. Thanks to the synergistic effect of the ZnO-NHC ​​support and the FeCoNiCuMo high-entropy alloy, the electrocatalyst of this invention performs excellently under these conditions. The ZnO nanoclusters promote the dissociation of neutral water molecules, providing active hydrogen and compensating for the insufficient proton supply under neutral conditions; while the specific electronic structure of the high-entropy alloy precisely modulates the reaction pathway, thereby simultaneously suppressing the HER side reaction thermodynamically and kinetically.

[0051] Compared with the prior art, the present invention has the following advantages: The FeCoNiCuMo@ZnO-NHC ​​high-entropy alloy electrocatalyst provided by this invention uses ZnO-NHC ​​as a support and fully retains the hexagonal rod-shaped hollow porous structure of Zn-MOF-74, which has high specific surface area, good conductivity and excellent structural stability. It provides a large number of attachment sites for high-entropy alloy nanoparticles, effectively increasing the electrochemically active surface area. At the same time, the multi-element synergistic effect of the pentagonal high-entropy alloy generates rich mixed valence states, precisely controls the electronic structure, optimizes the adsorption and desorption performance of reaction intermediates, and significantly suppresses hydrogen evolution side reactions, achieving a simultaneous improvement in the activity and selectivity of electrocatalytic nitrate reduction to ammonia.

[0052] This invention employs a rapid Joule heating method to prepare high-entropy alloy electrocatalysts, which has unique advantages such as extremely fast heating rate, short heating time, and uniform heating. It can achieve instantaneous reduction and alloying of metal salts, effectively inhibit the agglomeration and growth of metal particles, and ensure that high-entropy alloy nanoparticles are uniformly dispersed on the support surface. This method has low energy consumption, simple operation, and good experimental repeatability, making it suitable for large-scale preparation.

[0053] The FeCoNiCuMo@ZnO-NHC ​​high-entropy alloy electrocatalyst prepared in this invention exhibits excellent electrocatalytic performance: in a neutral mixed electrolyte of 0.1 mol / L KNO3 and 0.1 mol / L Na2SO4, the Faradaic efficiency reaches 92.6% at -0.8 V vs. RHE potential, and the ammonia yield reaches 3469.12 µg·h⁻¹. -1 ·mg -1 cat. The catalyst exhibits almost no decrease in current density during a 30-hour long-term electrolysis process, and shows minimal fluctuations in Faraday efficiency and ammonia yield during 15 cycle tests, demonstrating excellent electrochemical durability and promising prospects for industrial application.

[0054] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments, but it should not be construed as a limitation on the scope of protection of the present invention.

[0055] Example 1 This embodiment provides a MOF-derived high-entropy alloy electrocatalytic catalyst for the reduction of nitrate to ammonia, FeCoNiCuMo@ZnO-NHC, the preparation method of which includes the following steps: Step 1: Dissolve 0.6 g of 2,5-dihydroxyterephthalic acid in a mixed solution containing 0.75 mL of deionized water and 30 mL of DMF, and stir until completely dissolved to form solution A; dissolve 1.008 g of zinc acetate dihydrate in a mixed solution containing 0.75 mL of deionized water and 30 mL of DMF, and stir until completely dissolved to form solution B.

[0056] While stirring vigorously, slowly pour solution A into solution B, and continue stirring for 20 minutes to allow Zn to react. 2+ The ligands fully coordinate to form crystal nuclei. The mixture is transferred to a 100 mL PTFE-lined stainless steel autoclave, sealed, and heated at 100 °C for 24 h. After the reaction is complete, it is allowed to cool naturally to room temperature. The reaction solution is centrifuged at 8000 rpm for 5 min, and the yellow precipitate at the bottom is collected. The precipitate is washed at least 5 times with DMF and anhydrous methanol, centrifuged and the supernatant is discarded after each wash, until the supernatant is colorless and transparent. The washed precipitate is placed in a vacuum drying oven and dried under vacuum at 60 °C for 12 h to obtain a pale yellow powdery Zn-MOF-74 precursor.

[0057] Step 2: Spread the Zn-MOF-74 precursor evenly in an alumina crucible and place it in a tube furnace. Purge the furnace with nitrogen for 30 minutes to remove air, then heat to 800℃ at a heating rate of 5℃ / min and hold for 3 hours for pyrolysis. After pyrolysis, allow the furnace to cool naturally to room temperature, remove and grind to obtain a black powdered ZnO-NHC ​​support.

[0058] Step 3: Accurately weigh 0.2 g of ZnO-NHC ​​support and 0.24 g of the target metal acetylacetone salt in an equimolar ratio of 1:1.2 (ZnO-NHC ​​support to iron acetylacetone, cobalt acetylacetone, nickel acetylacetone, copper acetylacetone, and molybdenum acetylacetone). Add the mixture to 100 mL of anhydrous ethanol. Stir in a 60°C water bath for 6 h to allow the metal salt to be uniformly adsorbed onto the support surface. Then, allow the mixture to dry naturally to obtain a mixed powder.

[0059] Step 4: Spread the mixed powder evenly on 0.2 mm thick graphite paper, place it in the heating chamber of the Joule heating device, and heat it at 10°C under argon protection. 3 -10 4 The temperature was rapidly increased to 1200℃ at a rate of ℃ / s, held for 0.5 s, and then allowed to cool naturally to obtain a MOF-derived FeCoNiCuMo@ZnO-NHC ​​high-entropy alloy electrocatalyst.

[0060] Comparative Example 1 This comparative example provides a MOF-derived electrocatalytic nitrate reduction catalyst ZnO-NHC ​​for ammonia production, the preparation method of which includes the following steps: Step 1: Dissolve 0.6 g of 2,5-dihydroxyterephthalic acid in a mixed solution containing 0.75 mL of deionized water and 30 mL of DMF, and stir until completely dissolved to form solution A; dissolve 1.008 g of zinc acetate dihydrate in a mixed solution containing 0.75 mL of deionized water and 30 mL of DMF, and stir until completely dissolved to form solution B.

[0061] While stirring vigorously, slowly pour solution A into solution B, and continue stirring for 20 minutes to allow Zn to react. 2+ The ligands fully coordinate to form crystal nuclei. The mixture is transferred to a 100 mL PTFE-lined stainless steel autoclave, sealed, and heated at 100 °C for 24 h. After the reaction is complete, it is allowed to cool naturally to room temperature. The reaction solution is centrifuged at 8000 rpm for 5 min, and the yellow precipitate at the bottom is collected. The precipitate is washed at least 5 times with DMF and anhydrous methanol, centrifuged and the supernatant is discarded after each wash, until the supernatant is colorless and transparent. The washed precipitate is placed in a vacuum drying oven and dried under vacuum at 60 °C for 12 h to obtain a pale yellow powdery Zn-MOF-74 precursor.

[0062] Step 2: Spread the Zn-MOF-74 precursor evenly in an alumina crucible and place it in a tube furnace. Purge the furnace with nitrogen for 30 minutes to remove air, then heat to 800℃ at a heating rate of 5℃ / min and hold for 3 hours for pyrolysis. After pyrolysis, allow the furnace to cool naturally to room temperature, remove and grind to obtain a black powdered ZnO-NHC ​​support.

[0063] Comparative Example 2 This comparative example provides a MOF-derived alloy electrocatalytic catalyst for the reduction of nitrate to ammonia, FeCoNi@ZnO-NHC, whose preparation method includes the following steps: Steps 1 and 2 are the same as in Example 1.

[0064] Step 3: Accurately weigh 0.2 g of ZnO-NHC ​​support and 0.24 g of the target metal acetylacetone salt in an equimolar ratio of ZnO-NHC ​​support to iron acetylacetone, cobalt acetylacetone, and nickel acetylacetone (total mass ratio 1:1.2), and add them to 100 mL of anhydrous ethanol. Stir in a 60℃ water bath for 6 h to allow the metal salt to be uniformly adsorbed onto the support surface, and then allow to dry naturally to obtain a mixed powder.

[0065] Step 4: Spread the mixed powder evenly on 0.2 mm thick graphite paper, place it in the heating chamber of the Joule heating device, and heat it at 10°C under argon protection. 3 -10 4 The temperature was rapidly increased to 1200℃ at a rate of ℃ / s, held for 0.5 s, and then allowed to cool naturally to obtain a MOF-derived FeCoNi@ZnO-NHC ​​high-entropy alloy electrocatalyst.

[0066] Comparative Example 3 This comparative example provides a MOF-derived alloy electrocatalytic catalyst for the reduction of nitrate to ammonia, FeCoNiCu@ZnO-NHC, whose preparation method includes the following steps: Step 1 and Step 2 are both examples of 1.

[0067] Step 3: Accurately weigh 0.2 g of ZnO-NHC ​​support and 0.24 g of the target metal acetylacetone salt in an equimolar ratio of 1:1.2 (ZnO-NHC ​​support to iron acetylacetone, cobalt acetylacetone, nickel acetylacetone, and copper acetylacetone), and add them to 100 mL of anhydrous ethanol. Stir in a 60℃ water bath for 6 h to allow the metal salt to be uniformly adsorbed onto the support surface, and then allow to dry naturally to obtain a mixed powder.

[0068] Step 4: Spread the mixed powder evenly on 0.2 mm thick graphite paper, place it in the heating chamber of the Joule heating device, and heat it at 10°C under argon protection. 3 -10 4 The temperature was rapidly increased to 1200℃ at a rate of ℃ / s, held for 0.5 s, and then allowed to cool naturally to obtain a MOF-derived FeCoNiCu@ZnO-NHC ​​high-entropy alloy electrocatalyst.

[0069] Comparative Example 4 This comparative example provides a MOF-derived alloy electrocatalytic catalyst for the reduction of nitrate to ammonia, FeCoNiMo@ZnO-NHC, whose preparation method includes the following steps: Step 1 and Step 2 are both examples of 1.

[0070] Step 3: Accurately weigh 0.2 g of ZnO-NHC ​​support and 0.24 g of the target metal acetylacetone salt in an equimolar ratio of 1:1.2 (ZnO-NHC ​​support to iron acetylacetone, cobalt acetylacetone, nickel acetylacetone, and molybdenum acetylacetone). Add the mixture to 100 mL of anhydrous ethanol. Stir in a 60°C water bath for 6 h to allow the metal salt to be uniformly adsorbed onto the support surface. Then, allow the mixture to dry naturally to obtain a mixed powder.

[0071] Step 4: Spread the mixed powder evenly on 0.2 mm thick graphite paper, place it in the heating chamber of the Joule heating device, and heat it at 10°C under argon protection. 3-10 4 The temperature was rapidly increased to 1200℃ at a rate of ℃ / s, held for 0.5 s, and then allowed to cool naturally to obtain a MOF-derived FeCoNiMo@ZnO-NHC ​​high-entropy alloy electrocatalyst.

[0072] Performance verification 1. Morphological characteristics Figure 1 The figures show the XRD patterns of the electrocatalysts obtained in Example 1 and Comparative Examples 1-4 of this invention. As can be seen from the figures, the ZnO-NHC ​​support was successfully prepared and the high-entropy alloy was successfully loaded.

[0073] Depend on Figure 1 It can be seen that at 2θ=31.773°, 34.441°, 36.262°, 47.557°, 56.603°, 62.888°, 66.386°, 67.967°, and 69.099°, all four samples exhibit clear and sharp characteristic diffraction peaks. These peak positions are completely matched with the standard PDF card (#97-005-7450) of hexagonal wurtzite ZnO, corresponding to the typical crystal planes of ZnO such as (100), (002), (101), (102), (110), (103), (200), (112), and (201). The sharp peaks and absence of obvious impurity peaks indicate that the ZnO-NHC ​​support in all four composite materials maintains a highly ordered hexagonal wurtzite crystal structure with good crystal quality. This also directly confirms the successful synthesis and structural stability of the ZnO-NHC ​​support, showing no crystal phase transition or significant lattice destruction due to the loading of the high-entropy alloy. The gray shaded area in the figure corresponds to the characteristic diffraction peaks of the face-centered cubic (fcc) high-entropy alloy. The signal changes in this region intuitively reflect the loading and structural evolution of the high-entropy alloy on the ZnO-NHC ​​support. From bottom to top (i.e., from FeCoNi@ZnO-NHC ​​to FeCoNiCuMo@ZnO-NHC), as the number of doped metal elements increases (gradually transitioning from ternary FeCoNi to pentagonal FeCoNiCuMo), the intensity of the diffraction peaks corresponding to the high-entropy alloy shows a gradual increasing trend, and the peak shape becomes sharper. This indicates that the crystallinity of the high-entropy alloy significantly increases with the enrichment of elemental composition, further proving the successful formation and loading of the high-entropy alloy phase.

[0074] Figure 2 This is a scanning electron microscope (SEM) image of the ZnO nitrogen-doped porous hexagonal carbon support (ZnO-NHC) prepared in Example 1 of this invention. Figure 2 It can be seen that it fully retains the hexagonal rod-shaped macroscopic framework structure, but the rods exhibit significant transparency. This phenomenon originates from the pyrolysis of organic ligands into an N-doped porous carbon framework during the high-temperature carbonization process of the MOF precursor, while Zn... 2+The in-situ conversion to ZnO nanocrystals, with the low density of porous carbon and the fine structure of ZnO nanocrystals, together reduced the electron scattering intensity, directly confirming the successful implementation of the carbonization strategy. It also shows that the ZnO-NHC ​​support not only retains the three-dimensional conductive network of the precursor, but also achieves optimization of pore structure and conductivity through carbon doping.

[0075] Figure 3 This is a scanning electron microscope (SEM) image of the MOF-derived ZnO nitrogen-doped porous hexagonal carbon-supported FeCoNiCuMo pentagonal high-entropy alloy electrocatalyst (FeCoNiCuMo@ZnO-NHC) prepared in Example 1 of this invention. Figure 3 It can be seen that a dense array of nanoparticles is uniformly distributed on the surface of the hexagonal rod-shaped matrix of ZnO-NHC. These particles are high-entropy alloy nanoparticles formed by the instantaneous reduction of metal salts during Joule burning. Their dense and uniform distribution characteristics indicate that this method can achieve efficient reduction and anchoring of metal salts in a very short time.

[0076] Figure 4 This is a transmission electron microscope (TEM) image of the MOF-derived ZnO nitrogen-doped porous hexagonal carbon-supported FeCoNiCuMo pentagonal high-entropy alloy electrocatalyst (FeCoNiCuMo@ZnO-NHC) prepared in Example 1. Figure 4 It can be seen that the composite material maintains a good carrier-particle composite structure. The diameter of the high entropy alloy (HEA) nanoparticles is clearly observed to be between a few nanometers and tens of nanometers. The particles are tightly anchored on the ZnO-NHC ​​support surface and have a good loading state, which provides a guarantee for the rapid transport of electrons and reactants during electrocatalysis.

[0077] 2. Performance Characterization The electrocatalysts obtained in the examples and comparative examples were subjected to electrochemical tests.

[0078] The electrochemical testing system employs a three-electrode H-type dual-chamber electrolytic cell system, with parameter control achieved via a CHI 760E electrochemical workstation. The specific configuration is as follows: the working electrode is a catalyst-modified glassy carbon electrode (6 mm in diameter); the reference electrode is an Ag / AgCl (3 mol / L KCl) electrode; and the counter electrode is a platinum mesh electrode (2 × 2 cm² surface area). 2 The catalyst-supported electrode was prepared according to a standard procedure: 5 mg of catalyst powder was accurately weighed and dispersed in a mixed solvent of 490 μL ultrapure water and 490 μL anhydrous ethanol. 20 μL of 5 wt.% Nafion solution was added as a binder, and the mixture was ultrasonically dispersed for 30 minutes to form a homogeneous catalyst ink. 20 μL of the catalyst ink was uniformly coated onto the surface of a glassy carbon electrode substrate polished with nano-Al₂O₃ using a micropipette, and dried in an oven at 45°C to obtain the working electrode.

[0079] The electrochemical characterization in this embodiment follows the standard testing procedure: First, in a mixed electrolyte system of 0.1 mol / L KNO3 and 1 mol / L Na2SO4, linear sweep voltammetry (LSV) is used at 5 mV. s -1 Electrochemical window scanning was performed. After determining the effective potential window using LSV, continuous electrolysis was conducted for 2 h in constant potential mode using chronoamperometry to systematically evaluate the steady-state electrocatalytic nitrate reduction activity of the catalyst. All current density data are based on the geometric surface area of ​​the glassy carbon electrode (0.283 cm²). 2 The potential measurements were normalized, and all values ​​were collected with reference to the Ag / AgCl reference electrode (3 mol / L KCl). The reversible hydrogen electrode (RHE) potential was calibrated using the following formula: E(vs.RHE)=E(vs.Ag / AgCl)+0.197+0.0591×pH.

[0080] Table 1 Faraday efficiency

[0081] Table 2 Ammonia Yield

[0082] The ammonia yield in Table 2 is in µg. h -1 mg -1 cat. .

[0083] From Table 1, Table 2, Figure 5 and Figure 6 It can be seen that, based on the ternary alloy catalyst of iron, cobalt and nickel, adding copper alone will improve the ammonia production performance of the electrocatalyst, while adding molybdenum alone will reduce the ammonia production performance of the electrocatalyst. The electrocatalyst with both copper and molybdenum added has the optimal ammonia production performance.

[0084] Depend on Figure 7 and Figure 8 It can be seen that the MOF-derived high-entropy alloy electrocatalyst prepared in Example 1 has excellent electrochemical stability. During the long-term electrolysis process of 30 hours, the current density hardly decayed, and the Faraday efficiency and ammonia yield fluctuated very little in 15 cycles.

[0085] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A MOF-derived high-entropy alloy electrocatalyst for the reduction of nitrate to ammonia, characterized in that, Includes a carrier and high-entropy alloy nanoparticles loaded on the surface of the carrier; The carrier is nitrogen-doped porous hexagonal carbon ZnO, and the high-entropy alloy is composed of five elements, Fe, Co, Ni, Cu and Mo, in equimolar ratios.

2. The MOF-derived high-entropy alloy electrocatalyst for nitrate reduction to ammonia as described in claim 1, characterized in that, The high-entropy alloy nanoparticles have a diameter of 30-40 nm.

3. The MOF-derived high-entropy alloy electrocatalyst for nitrate reduction to ammonia as described in claim 1, characterized in that, The high-entropy alloy nanoparticles have a face-centered cubic crystal structure.

4. The MOF-derived high-entropy alloy electrocatalyst for nitrate reduction to ammonia as described in claim 1, characterized in that, Nitrogen-doped porous hexagonal carbon ZnO retains the hexagonal rod-like morphology of Zn-MOF-74.

5. A method for preparing a MOF-derived high-entropy alloy electrocatalyst for nitrate reduction to ammonia as described in any one of claims 1-4, characterized in that, include: A precursor was obtained by mixing a 2,5-dihydroxyterephthalic acid solution and a zinc source solution and then carrying out a hydrothermal reaction. The precursor was pyrolyzed under a nitrogen atmosphere to obtain nitrogen-doped porous hexagonal carbon ZnO. Nitrogen-doped porous hexagonal carbon ZnO was mixed with Fe, Co, Ni, Cu and Mo salts in an equimolar ratio to obtain a mixed powder. The mixed powder was heat-treated using a Joule heating device under a protective atmosphere at a heating rate of 10°C. 3 -10 4 A high-entropy alloy electrocatalyst for the reduction of nitrate to ammonia was obtained by heating at ℃ / s, with a heating temperature of 1100-1300℃ and a heating time of 0.1-1 s.

6. The preparation method according to claim 5, characterized in that, The hydrothermal reaction involving the mixing of 2,5-dihydroxyterephthalic acid solution and zinc source solution includes: Dissolve 2,5-dihydroxyterephthalic acid in a mixed solution of water and N,N-dimethylformamide, and stir until completely dissolved to form solution A; Dissolve zinc acetate dihydrate in a mixed solution of water and N,N-dimethylformamide, and stir until completely dissolved to form solution B; While stirring, pour solution A into solution B, continue stirring, and a mixed solution is obtained; The mixed solution was subjected to a hydrothermal reaction, and after the reaction was completed, it was naturally cooled to room temperature to obtain the precursor. Preferably, the mass ratio of the 2,5-dihydroxyterephthalic acid solution to zinc acetate dihydrate is 0.6:0.9-1.1, more preferably 0.6:1.008; Preferably, the hydrothermal reaction is carried out at a temperature of 95-105℃ for a time of 20-30 h; Preferably, after the hydrothermal reaction is completed, the precipitate is separated, collected, and then washed and dried in sequence.

7. The preparation method according to claim 5, characterized in that, The pyrolysis process involves a heating rate of 3-7℃ / min, a pyrolysis temperature of 750-850℃, and a pyrolysis time of 2-4 h. After pyrolysis, the product is naturally cooled to room temperature in the furnace, removed, and ground to obtain nitrogen-doped porous hexagonal carbon ZnO.

8. The preparation method according to claim 5, characterized in that, The salt is acetylacetone salt; Preferably, the mixing of nitrogen-doped ZnO porous hexagonal carbon with equimolar amounts of Fe, Co, Ni, Cu, and Mo salts comprises: Weigh out nitrogen-doped porous hexagonal carbon ZnO and Fe, Co, Ni, Cu, and Mo acetylacetone salts in an equimolar ratio. The mass ratio of ZnO nitrogen-doped porous hexagonal carbon to the total mass of the target metal salts is (0.8-1.2):1.

2. After weighing, add the mixture to an organic solvent, stir at 50-70℃, and dry to obtain a mixed powder. Preferably, the organic solvent is anhydrous ethanol.

9. The application of the MOF-derived high-entropy alloy electrocatalytic nitrate reduction to ammonia catalyst according to any one of claims 1-4 in the electrocatalytic nitrate reduction to ammonia process.

10. A method for producing ammonia by electrocatalytic reduction of nitrate, characterized in that, include: The MOF-derived high-entropy alloy electrocatalytic nitrate reduction to ammonia catalyst according to any one of claims 1-4 is used as the catalytic active component for electrocatalytic nitrate reduction to ammonia, reducing nitrate ions in nitrate solution to ammonia in a neutral electrolyte system.